Parasioid Wasps of Eulophinae (Hymenoptera: Eulophidae) in Nusa TenggaraRA TIMUR, INDONESIA - Rosichon Ubaidillah (BRIN Publishing (Penerbit BRIN), 2003)
Eulopliid parasitoid wasps of the Enlophinnc III Nusa Tenggara TIII/llr, i ndonesia, were studied taxonomicallu. A total of15 species 111 nine gellern are recorded. From those species eight are described neui toscience. Keys to gel/era and species are presented.